ANT INTELLIGENCE ROUTING - Chye Ong Gan; K. Daniel Wong; Wei-Le Woon (Universitas Gadjah Mada, 2008)
We introduce AIR, a new ant-based routing protocol for ad hoc wireless networks. AIR incorporates recent technology advances in ad hoc routing protocols, such as ring-based searching and third-party reply, while retaining the characteristics and benefits of ant-based routing protocols, including probabilistic routing tables and pheromone evaporation. In addition, we combine the best features of previous ant-based routing protocols with new features like update ants and two-way route establishment, to further improve performance. We compare the performance of AIR against AODV and DSR using appropriately chosen simulations, the results of which are presented and discussed. We find that AIR is especially useful for ad hoc networks requiring low end-to-end delay where mobility rates are high.